2009
DOI: 10.1177/0748233709345937
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of ethanol to acetaldehyde and increased susceptibility to oxidative stress could play a role in the ovarian tissue cell injury promoted by alcohol drinking

Abstract: It is known that drinking alcohol can lead to reproductive problems in women. In this study, we analyzed the possibility that part of those effects were mediated through alterations of ovarian function related to ethanol oxidation to acetaldehyde occurring in situ. Biotransformation in the rat ovary cytosolic fraction was partially inhibited by allopurinol, suggesting the participation of xanthine oxidoreductase in the process. Microsomal pathway was of enzymatic nature, requiring nicotinamide adenine dinucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Long-term moderate alcohol consumption was also shown to decrease ovarian reserve which was associated with increased FSH levels 65 . Faut and colleagues 66 have suggested that an in-situ metabolism of ethanol to acetaldehyde increases the susceptibility of rat ovarian tissue to oxidative stress and leads to cell damage and ovarian dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term moderate alcohol consumption was also shown to decrease ovarian reserve which was associated with increased FSH levels 65 . Faut and colleagues 66 have suggested that an in-situ metabolism of ethanol to acetaldehyde increases the susceptibility of rat ovarian tissue to oxidative stress and leads to cell damage and ovarian dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues in vivo are simultaneously exposed to ethanol and acetaldehyde due to ubiquitous distribution of alcohol dehydrogenase (ADH)3, CYP2E14 and catalase56, all known to metabolize ethanol into acetaldehyde. Mounting evidence indicates that ethanol metabolism by ADH into acetaldehyde plays a crucial role in alcoholic tissue injury in many organs78910111213. Studies reported so far have evaluated the effect of either ethanol or acetaldehyde on tissue functions, including the epithelial barrier function.…”
mentioning
confidence: 99%
“…Ovarian and mammary tissues were already studied in more detail, and initial efforts directed to uterine horn were also performed [1, 23, 34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Not all the effects of alcohol drinking in different target organs can be explained in terms of endocrine disturbances [12, 23, 36]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation